Characterization of Silver Nanoparticles Internalized by Arabidopsis Plants Using Single Particle ICP-MS Analysis - Bao, Dongping; Oh, Zhen Guo; Chen, Zhong (Frontiers in Plant Science, 2016)
Plants act as a crucial interface between humans and their environment. The wide use of nanoparticles (NPs) has raised great concerns about their potential impacts on crop health and food safety, leading to an emerging research theme about the interaction between plants and NPs. However, up to this day even the basic issues concerning the eventual fate and characteristics of NPs after internalization are not clearly delineated due to the lack of a well-established technique for the quantitative analysis of NPs in plant tissues. We endeavored to combine a quantitative approach for NP analysis in plant tissues with TEM to localize the NPs. After using an enzymatic digestion to release the NPs from plant matrices, single particle-inductively coupled plasma-mass spectrometry (SP-ICP-MS) is employed to determine the size distribution of silver nanoparticles (Ag NPs) in tissues of the model plant Arabidopsis thaliana after exposure to 10 nm Ag NPs. Our results show that Macerozyme R-10 treatment can release Ag NPs from Arabidopsis plants without changing the size of Ag NPs. The characteristics of Ag NPs obtained by SP-ICP-MS in both roots and shoots are in agreement with our transmission electron micrographs, demonstrating that the combination of an enzymatic digestion procedure with SP-ICP-MS is a powerful technique for quantitative determination of NPs in plant tissues. Our data reveal that Ag NPs tend to accumulate predominantly in the apoplast of root tissues whereby a minor portion is transported to shoot tissues. Furthermore, the fact that the measured size distribution of Ag NPs in plant tissue is centered at around 20.70 nm, which is larger than the initial 12.84 nm NP diameter, strongly implies that many internalized Ag NPs do not exist as intact individual particles anymore but are aggregated and/or biotransformed in the plant instead.